Cichlid species‐area relationships are shaped by adaptive radiations that scale with area. (6th March 2014) - Wagner, Catherine E.; Harmon, Luke J.; Seehausen, Ole; Morlon, Helene
Abstract A positive relationship between species richness and island size is thought to emerge from an equilibrium between immigration and extinction rates, but the influence of species diversification on the form of this relationship is poorly understood. Here, we show that within‐lake adaptive radiation strongly modifies the species‐area relationship for African cichlid fishes. The total number of species derived from in situ speciation increases with lake size, resulting in faunas orders of magnitude higher in species richness than faunas assembled by immigration alone. Multivariate models provide evidence for added influence of lake depth on the species‐area relationship. Diversity of clades representing within‐lake radiations show responses to lake area, depth and energy consistent with limitation by these factors, suggesting that ecological factors influence the species richness of radiating clades within these ecosystems. Together, these processes produce lake fish faunas with highly variable composition, but with diversities that are well predicted by environmental variables.